Masters and slaves: A matching approach with heterogeneous workers - Bianca Willert (Universität Rostock, Institut für Volkswirtschaftslehre, 2018)
At present, most countries have officially ratified the ILO Convention concerning forced or compulsory labor; however, serfdom is still present in the twenty-first century. This paper addresses the questions of how situations of modern slavery arise and how oppressors select their victims. The analytical framework is a labor-market model in which masters and slaves are matched via a matching function. In contrast to the standard matching model, not the workers exert effort to find jobs but the employers exert effort to find and hire slaves. Workers are heterogeneous regarding their "slavability", which is ex-ante unknown to the potential employers. Employers exert effort to recruit slaves. The employer's decision whether and to what extent to engage in forced labor depends on governmental labor protection and on the probability of detection. Moreover, the model includes the possibility of bribery such that an employer can avoid sanctions if illicit behavior is detected. The model is solved and the impact of policy variables and other exogenous parameters on the firms' activities are investigated.
Keywords: J23; J47; J71; 330; Coerced Labor; Modern Slavery; Matching